RETRAKSI: Analisis Parameter Fisika-Kimia untuk Kepentingan Rehabilitasi Ekosistem Mangrove di Pesisir Pulau Bungkutoko Kota Kendari - Yasin, Asramid; Pristya, Terry Y. R. (Universitas Diponegoro, 2020)
Retraction NotificationAfter going through a careful process of review and attention to the article that have been published in Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, Volume 17 Issues 1 pp 1-18 in March 2020, the editor board decided to retract this article because of its violence to the Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan's ethical code.This article has been submitted at the same time in the Journal of Green Growth and Environmental Management. Before being published, we have made an effort to detect plagiarism using the turnitin application twice, on 30 November 2019 (23% of similarity) and 30 August 2019 (18% of similarity). On January 2, 2020, the corresponding author corrected and editted the article and the Editor published the article in the